DILEMMA IN GENDER ASSIGNMENT IN VANISHING TESTIS SYNDROME: REPORT OF TWO CASES - L, Annie; H, Janet Yeowhua; W, Sze Lyn Jeanne; MS, Nalini; M, Rashdan Zaki; MA, Noor Arliena; T, Sze Teik; T, Pian; MZ, Fuziah (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Vanishing testis syndrome, or Testicular regression syndrome (TRS) is a developmental anomaly characterized by the absence of one or both testicles with partial or complete absence of testicular tissues. Vanishing testis syndrome may vary from normal male with unilateral nonpalpable testis through phenotypic male with micropenis, to phenotypic female. The phenotype depends on the extend and timing of the intrauterine accident in relation to sexual development. Here we present 2 cases of vanishing testis syndrome with different gender assignment. CASE 1 10-month-old baby with chromosome 46XY presented with genital ambiguity with phallus-like structure, labioscrotal fold and non-palpable gonads. Follicular stimulating hormone (FSH) and luteinizing hormone (LH) level suggest of gonadal failure. Beta human chorionic gonadotropin stimulation test shows poor testosterone response. Laparoscopic exploration revealed bilateral spermatic cord and vessels with atrophic testes. In view of severe undervirilised phenotype, parents registered child as a female. CASE 2 12-year-old child already registered as a boy, was referred for bilateral undescended testes and micropenis. Chromosome is 46XY. Laparoscopic exploration revealed atrophic testicular tissues at the end of spermatic cord. Histopathological examination shows structure resemble vas deferens and benign adrenal rest tissues. The child was given testosterone replacement during pubertal age. CONCLUSION Diagnosis of vanishing testis is based on clinically nonpalpable testis with a blind-ending spermatic cord. It has a typical clinical and histopathological characteristic, but with a wide spectrum of clinical presentation and phenotype. The degree of masculinization depends on the duration of testicular function prior to its loss. Thus, gender assignment needs careful consideration and involves extensive discussion among the parents and multidisciplinary teams. Long-term outcome of clinical status, gender identity and sexual orientation need to be monitored.